Rise of humanism in classical Islam and the Christian West - "Makdisi, George" (London, 1990)
This is a survey of the historical development of two major intellectual movements. It shows that these movements, which have long been considered as of exclusively Western origin, in fact have their roots deep in Islamic soil. Professor Makdisi argues that scholasticism (the movement of the school guilds in the Middle Ages), and humanism (a movement from the Italian Renaissance) came to the Christian West around 1100 through Spain, via an influx of Arabic books from Classical Islam.
Keywords: Humanism